Do you feel prepared? EFL learners' readiness for online learning and self-directed learning ability - Genc, Gulten; Kutlu, Muhammed Nazif; Kirmizibayrak, Ozge (Bastas Publ Ltd - Uk, 2024)
In recent years, the widespread use of online learning environments and tools, especially with the outbreak of the COVID-19 pandemic, has brought students' readiness for online learning and their ability to manage their own learning processes to the fore. This study aims to investigate the online learning readiness (OLR) and self -directed learning skills of English language learners at a state university in Turkey. For this purpose, a cross-sectional, descriptive study methodology was employed. The study group consisted of 202 randomly selected first -year volunteer students. An information form and two scales were used to collect data. Additionally, the effects of some demographic factors on EFL students' OLR and self -directed learning skills were also investigated. The results of the study revealed that university students have a moderate level of self -directed learning and readiness to learn in the online environment. As another result of the study, it was determined that various independent variables had an impact on the participants' OLR levels. In parallel with the findings of the study, some pedagogical strategies were discussed and suggested.
Keywords: readiness for online learning; self-directed learning; English as a foreign language; higher education; technology in education